2020
DOI: 10.3389/fphar.2020.532457
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hyaluronic Acid-Based Nanocarrier Incorporating Doxorubicin and Cisplatin as a pH-Sensitive and CD44-Targeted Anti-Breast Cancer Drug Delivery System

Abstract: Tumor-targeting nanomaterial-based chemotherapeutic drug delivery systems have been shown to represent an efficacious approach for the treatment of cancer because of their stability in blood circulation and predictable delivery patterns, enhanced tumor-selective drug accumulation, and decreased toxicity to normal tissues. The cell-surface transmembrane glycoprotein CD44 binds to the extracellular domain of hyaluronic acid (HA), and is overexpressed in breast, ovarian, lung, and stomach cancer. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…Anionic liposomes were shown to accumulate in BM and were then predominantly adsorbed by leukemic cells [ 154 ]. Hyaluronic acid, which shows a high binding affinity for the CD44 adhesion molecule, is present at enhanced concentrations in a variety of tumors and was also proposed for NC modification [ 159 , 160 ]. Experimental trials of novel delivery methods for CBD in cancer therapy are still scarce but have demonstrated promising results ( Table 3 ) [ 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ].…”
Section: Concerning Better Cbd Delivery For Cancer Therapymentioning
confidence: 99%
“…Anionic liposomes were shown to accumulate in BM and were then predominantly adsorbed by leukemic cells [ 154 ]. Hyaluronic acid, which shows a high binding affinity for the CD44 adhesion molecule, is present at enhanced concentrations in a variety of tumors and was also proposed for NC modification [ 159 , 160 ]. Experimental trials of novel delivery methods for CBD in cancer therapy are still scarce but have demonstrated promising results ( Table 3 ) [ 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ].…”
Section: Concerning Better Cbd Delivery For Cancer Therapymentioning
confidence: 99%
“…HA, also named as hyaluronic acid and hyaluronate, is a linear and non-sulfated PS composed of repeating disaccharides of D-glucuronic acid and N-acetyl-D-glucosamine units (Jeong et al, 2008). HA is highly negatively charged and a major component of the extracellular matrix of mammalian cells (Debele et al, 2016;Miao et al, 2018;Yu et al, 2020). Due to its excellent biocompatibility, low cost, non-immunogenicity, and water-binding properties, HA has been used for dermal filler, joint lubrication, prevention of surgical adhesion, dietary supplements, and eye drops (Valachova et al, 2016;Kim et al, 2017).…”
Section: Self-assembled Hyaluronan (Ha) Ngmentioning
confidence: 99%
“…Interestingly, HA and cisplatin could also be co-assembled with a second drug to form multidrug NG (Figure 1C), thus easily realizing the combination therapy especially for cancer . The cationic-aromatic drugs (CA drugs) containing aromatic ring and positive charges, such as chemotherapeutics (Zhang et al, , 2018Yu et al, 2020;Ma et al, 2021), kinase inhibitors , and photosensitizers/dyes (Zhang and Tung, 2018a), could be easily self-assembled into the HA/Cis NG. The positive charges of CA drugs are believed to interact with HA through electrostatic interaction while the aromatic ring contributes to the hydrophobic interaction and π-π stacking of drugs, which collectively facilitates the encapsulation of CA drug into the NG.…”
Section: Self-assembled Hyaluronan (Ha) Ngmentioning
confidence: 99%
“…As micelas de AH-DOX-CDDP, analisadas em um modelo de camundongo com câncer de mama, demonstraram menor toxicidade e melhores efeitos inibitórios do que drogas livres, de acordo com os testes utilizando imunofluorescência e análise histológica. Esse resultado demonstra que o composto AH-DOX-CDDP representa um sistema de medicamento animador, com excelente biocompatibilidade e biodegradação, relatando a promissora aplicação dessa medicação em quimioterapia para câncer de mama (Yu, 2020).…”
Section: Nanopartículas Micelaresunclassified